Does social capital travel? Influences on the life satisfaction of young people living in England and Spain - Morgan Antony R; Rivera Francisco; Moreno Carmen; Haglund Bo JA (BMC, 2012)
Abstract Background This study used a social capital framework to examine the relationship between a set of potential protective ('health assets') factors and the wellbeing of 15 year adolescents living in Spain and England. The overall purpose of the study was to compare the consistency of these relationships between countries and to investigate their respective relative importance. Methods Data were drawn from the 2002, English and Spanish components of the WHO Health Behaviour in School-Aged Children (HBSC) survey A total of 3,591 respondents (1884, Spain; 1707, England) aged 15, drawn from random samples of students in 215 and 80 schools respectively were included in the study. A series of univariate, bivariate and multivariate (general linear modelling and decision tree) analyses were used to establish the relationships. Results Results showed that the wellbeing of Spanish and English adolescents is similar and good. Three measures of social capital and 2 measures of social support were found to be important factors in the general linear model. Namely, family autonomy and control; family and school sense of belonging; and social support at home and school. However, there were differences in how the sub components of social capital manifest themselves in each country--feelings of autonomy of control, were more important in England and social support factors in Spain. Conclusions There is some evidence to suggest that social capital (and its related concept of social support) do travel and are applicable to young people living in Spain and England. Given the different constellation of assets found in each country, it is not possible to define exactly the precise formula for applying social capital across cultures. This should more appropriately be defined at the programme planning stage.